PI16 attenuates response to sorafenib and represents a predictive biomarker in hepatocellular carcinoma - Pusen Wang; Zhongyi Jiang; Xueni Liu; Kanru Yu; Chunguang Wang; Hao Li; Lin Zhong (Cancer Medicine)
Abstract Sorafenib has become the only FDA‐approved first‐line therapy for advanced hepatocellular carcinoma (HCC) for more than 10 years, but there is still no validated predictive or prognostic marker. Peptidase inhibitor 16 (PI16) is a functionally unknown gene in cancer research. This study aimed to determine the exact function of PI16 in HCC and whether it can represent as a biomarker for sorafenib response. We found that PI16 was over expressed in HCC tissues vs paired normal tissues. PI16 knockdown sensitize HCC cells to sorafenib treatment both in vitro and in vivo, whereas ectopic PI16 expression produced the opposite effect. Mechanistically, PI16 could suppress p38 MAPK/caspase‐dependent apoptosis in this process, and p38 MAPK inhibitor reversed the sorafenib sensitive phenotype caused by PI16 inhibition. Clinically, immunohistochemistry was used to detect PI16 levels in resected patients with HCC prior to sorafenib treatment. We showed that high PI16 levels represented an independent risk factor for disease progression in patients treated with sorafenib. Patients with low PI16 showed significantly better progression free survival and overall survival after sorafenib therapy. In conclusion, PI16 attenuates response to sorafenib treatment in HCC, and may be a helpful prognostic biomarker of sorafenib treatment.